Optimization of machining parameters for minimization of roundness error in deep hole drilling using minimum quantity lubricant - Kamaruzaman, A. F. (EDP Sciences, 2016)
This paper presents an experimental investigation of deep hole drilling using CNC milling machine. This experiment investigates the effect of machining parameters which are spindle speed, feed rate and depth of hole using minimum quantity lubricant on the roundness error. The experiment was designed using two level full factorial with four center point. Finally, the machining parameters were optimized in obtaining the minimum value of roundness error. The minimum value of roundness error for deep hole drilling is 0.0266 at the spindle speed is 800 rpm, feed rate is 60 mm/min, depth of hole is 70 mm and minimum quantity lubricant is 30ml/hr.